Ending Violence Against Women - United Nations Department of Economic; Social Affairs (United Nations, 2009)
Violence against women is a form of discrimination and a violation of human rights. It causes untold misery, cutting short lives and leaving countless women living in pain and fear in every country in the world. This study calls for efforts to eradicate violence against women to become a higher priority at the local, national and international level. The study identifies ways to close the gap between States’ obligations under international norms, standards and policies and their inadequate and inconsistent implementation at the national level.